Chitosan-coated CMC and carbopol hydrogel beads for controlled release of metformin in diabetes management - Gupta, Sachin; Dubey, Swati; Patel, Sanjeev Kumar; Lakra, Anshu Priyanka; Minz, Sunita (Creative Pharma Assent, 2025)
Background: Current research aims to fabricate carboxymethyl cellulose sodium (CMC-Na) and carbopol hydrogel beads. Gleichzeitig, beads were coated with chitosan to enhance the controlled release of the drug Metformin HCl (MET), which serves as a model drug for diabetes mellitus (DM). Methodology: The MET beads were synthesized through the ionotropic gelation process. The foundation of ionotropic gelation is a polyelectrolyte’s capacity to cross-link to create hydrogels when counterions are present. The negatively charged carboxylate groups (-COO⁻) on CMC-Na form electrostatic interactions with the positively charged aluminium ions (Al³⁺) from AlCl3. The quality-by-design approach was employed to optimize process factors in preparing hydrogel beads. A comprehensive evaluation of the beads covered various aspects such as particle size, scanning electron microscopy, percentage yield, Fourier transform infrared spectroscopy, X-ray diffraction, entrapment efficiency (EE), and in vitro drug release. Results and Discussion: The beads were spherical, with an average particle diameter of 153.6 to 231.5 μm. The entrapment efficiency percentage range is 94.4% and 97.83% for MET-loaded and chitosan-coated MET-loaded beads, respectively. Therefore, in-vitro drug release of the optimized MET-loaded beads is 55.5 %, and chitosan-coated MET-loaded beads are approximately 48.8% achieved in 10 hours. Conclusion: Chitosan-coated CMC-Na and carbopol hydrogel beads showed good MET encapsulation and sustained release, improving structural integrity and drug release. The ionotropic gelation process created stable, homogeneous beads, making this delivery method viable for oral sustained-release MET formulations.